The effectıveness of work from home (wfh) agaınst employee performance - Muhammad Donal Mon (KINERJA, 2021)
The aim of this study is to analyze effective work from home on the leadership, competency, training, and technology to employee performance. The design used is hypothesis testing using Statistical Package for the Social Sciences(SPSS). The population and respondents in this study was manufacturing employee. The results of the study show that the leadership has no significant effect on employee performance with significant = 0.360 and competency has significant affect to employee performance with significant value = 0,036 results on training has significant effect on employee performance with significant 0,005, and technology also has significant effect on employee performance with value of significant is 0,000. The results show that between leadership, competency, training, and technology as together influence employee performance with significant 0,000. Based on result for adjustedR square can be explain at 51,7% is influenced by the four variables (Leadership, Competency, Training, and Technology) to employee performance, the other 48.3% is the contribution of other variables not included in this research. According results testing in this research training, facility and technology significant impact on employee performance. Next research model can be explain with mediating variabel to make sure and increase adjustedR square results for example variabel the role of organizational commitment in organizational structure, organizational strategy and management during Covid 19 new era.